Comparison of two different constitutive equations for hot deformation of AZ91 magnesium alloy. Issue 1 (1st December 2022) - He, Zhongtao; Xu, Chun
Abstract: AZ91 magnesium alloy is usually processed by casting because of its high strength and poor plasticity. Therefore, it is difficult to adopt the conventional rolling method for processing. In order to improve its processing plasticity, the content of some alloying elements is changed based on their conventional composition. On this basis, this project researches its thermal processing behavior and establishes relevant models. Gleeble-1500D thermal simulator was used for operation, the experimental conditions were 300 400°C and the strain rate was 0.01 10°C/s, and compression capacity of 70%, self-developed hot compression simulation experiment of AZ91 magnesium alloy was carried out. The research results proved that the magnesium alloy is sensitive to strain rate. For the sake of better fit true stress-strain curve of AZ91 magnesium material, modified Arrhenius equation and modified peak stress equation was used for prediction. The results show that the modified peak stress equation fits well when the strain rate is low. However, the fitting effect is poor when strain rate is 10°C/s.